Case report: Primary intracranial mucosa-associated lymphoid tissue lymphoma presenting as two primary tumors involving the cavernous sinus and extra-axial dura, respectively - Tian, Shiyun; Pan, Tao; Gao, Bingbing; Li, Wanyao; Liu, Jiashen; Zou, Kun; Miao, Yanwei (Frontiers in Oncology, 2023)
Primary intracranial mucosa-associated lymphoid tissue (MALT) lymphoma is a rare type of brain tumor, with only a few reported cases worldwide, mostly have only one lesion with conventional MRI findings. Here, we present a special case of intracranial MALT lymphoma with two mass lesions radiographically consistent with meningiomas on MRI before the operation. A 66-year-old female was admitted to the hospital with intermittent right facial pain for one year, aggravated for the last month. Brain MRI showed two extracerebral solid masses with similar MR signal intensity. One mass was crescent-shaped beneath the skull, the other was in the cavernous sinus area. T1WI and T2WI were iso-intensity, intense homogeneous enhancement after contrast agent injection. Both lesions showed hyperintensity in amide proton transfer weighted (APTw) images. The two masses were all surgical resected. The postoperative pathology indicated extranodal marginal zone B cell lymphoma (EMZL) of mucosa-associated lymphoid tissue (MALT). To improve awareness of intracranial MALT lymphoma in the differential diagnosis of extra-axial lesions among clinicians, we present this report and briefly summarize previously reported cases to describe the clinical, pathological, radiological, and treatment features.